Meg Follows a Dream 1844 - Lutz, Norma Jean; Nang ChanYeema (Uhrichsville, Ohio USA Barbour Publishing, Inc., 2004)
Will Meg's family ever realize that She wants to pursue her dream of art?
Keywords: Adult Fiction